3-D finite element calculation of electric field enhancement for nanostructures fabrication mechanism on silicon surface with AFM tip induced local anodic oxidation. Issue 190 (13th June 2018) - Theogene, Barayavuga; Cui, Jianlei; Wang, Xuewen; Wang, Wenjun; Mei, Xuesong; Yi, Peiyun; Yang, Xinju; He, Xiaoqiao; Xie, Hui
ABSTRACT: The atomic force microscope (AFM) can be used in dynamic tipping mode as an effective lithography technique capable of manufacturing nanometer sized devices on the surface of a silicon wafer with a higher resolution surface characterization. The most difficult challenge in fabrication of nanostructure based on AFM nano-oxidation approach is the way of controlling an electric field between a cantilever probe tip and a silicon wafer. A water bridge builds up between the tip and the wafer, resulting in the oxidation due to the high electric field in the region. A reconstructive AFM system for nano-oxidation with a tapping model, implemented in an air, was developed. The presented AFM implements the increasing of electric field intensity by analyzing the impact voltage from −1 V to −5 V, electric field, and ion concentrations at the ambient/oxide and oxide/silicon interfaces, while the growth of thin oxides assumes a single liquid/silicon interface, which is modeled as an infinitely long conducting plane. Therefore, particle distribution for the surface charge density is generated for topography simulations. Based on the control-parameters, an enhanced electrical field of up to 10 10 V/m can be obtained, which provides a powerful support for controllable experimental study of nanostructures fabrication with AFM tip induced local anodic oxidation. This showed the dependence of applied voltage types and various nanostructures and life time of AFM tip, by controlling tip-sample position in nanolithography processes is an important factor for controlling the aspect electric field distribution. And the effect of different parameters on enhancement distribution was performed and analyzed in this paper.